THE RESILIENCE OF MUSLIM IDENTITY AND THE AWARENESS OF HALAL PRINCIPLES AMONG INDONESIAN MIGRANT WORKERS (IMWS) IN SOUTH KOREA - Rahma, Awalia; Maulani, Abdullah; Rohayati, Tati; Yessie Kualasari (Balai Penelitian dan Pengembangan Agama Jakarta, 2024)
This article discusses the resilience of Muslim identity and the awareness of halal principles among Indonesian Migrant Workers (IMWs) in South Korea. As a developed country with strong economic growth, South Korea has become an important destination for migrating Indonesian Muslim communities. By applying symbolic interaction theory, this research provides insight into understanding the role of religion in social interactions, identity formation, and the interpretation of halal products by IMWs and other social actors in the Korean environment. The research findings on IMWs indicate that there are at least two attitudes among the Indonesian Muslim diaspora in South Korea regarding their Islamic identity as measured by their awareness of halal principles. The first attitude is selective and strictly adheres to the religious values prevalent in Indonesia. The second attitude is a permissive one, where an Indonesian Muslim diaspora makes efforts to adapt their values to the local culture as long as they do not violate clear boundaries in Islamic law.